Stabilometric Correlates of Motor and Motor Imagery Expertise - Di Rienzo, Franck; Joassy, Pierric; Ferreira Dias Kanthack, Thiago; Moncel, François; Mercier, Quentin; Collet, Christian; Guillot, Aymeric (Frontiers in Human Neuroscience, 2022)
Motor Imagery (MI) reproduces cognitive operations associated with the actual motor preparation and execution. Postural recordings during MI reflect somatic motor commands targeting peripheral effectors involved in balance control. However, how these relate to the actual motor expertise and may vary along with the MI modality is still debated. In the present experiment, two groups of expert and non-expert gymnasts underwent stabilometric assessments while performing physically and mentally a balance skill. We implemented psychometric measures of MI ability, while stabilometric variables were calculated from center of pressure (COP) oscillations. Psychometric evaluations revealed greater MI ability in experts, specifically for the visual modality. Experts exhibited reduced surface COP oscillations in the antero-posterior axis compared to non-experts during the balance skill (14.90 %, 95% CI 34.48 to 4.68, p < 0.05). Experts further exhibited reduced length of COP displacement in the antero-posterior axis and as a function of the displacement area during visual and kinesthetic MI compared to the control condition (20.51%, 95% CI 0.99 to 40.03 and 21.85%, 95% CI 2.33 to 41.37, respectively, both p < 0.05). Predictive relationships were found between the stabilometric correlates of visual MI and physical practice of the balance skill, as well as between the stabilometric correlates of kinesthetic MI and the training experience in experts. Present results provide original stabilometric insights into the relationships between MI and expertise level. While data support the incomplete inhibition of postural commands during MI, whether postural responses during MI of various modalities mirror the level of motor expertise remains unclear.